Efeitos do ambiente enriquecido na mÁxima fase estÁvel do lactato de ratos wistar - Jordão, Lucas Figueiredo; Barbieri, Ricardo Augusto [UNESP]; De Assis, Welton Ferreira [UNESP]; Higino, Wonder Passoni; Santos, Julio Wilson Dos [UNESP]; De Almeida Leme, José Alexandre Curiacos [UNESP] (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2015)
The enriched environment (EE) is a combination of stimulations inserted in the cage, such as tunnels, exercise wheel and color objects, increased cage size and the number of rats. Although the EE can be promoter of physical activity (PA), the literature lacks studies showing the effects of this accumulation of PA in the rats. In this way, the present study aims to investigate the effects of EE on maximal lactate steady state in rats. To this, adult Wistar rats were randomly distributed into control group (CG), kept in conventional cages, and EE group (EEG), kept in enriched cages. Before and after the experimental period (six weeks) the animals were submitted for the maximal lactate steady state (MLSS) test. In the last week, length and body mass was measured. At the end of the experimental period, after euthanasia, blood sample was collected for the analyses of glucose and heart was weighted. To statistical analyses, after the test of normality, the parametric results were analyzed by Student's t test and nonparametric through Mann-Whintey test. There were no differences in serum glucose, body length, body and heart mass. The groups presented similar MLSS at beginning of experiment, however, MLSS load was higher in EE than CG at end of experiment. In conclusion, PA performed in the enriched cage increased the aerobic capacity in comparing to the conventional cage, even in the absence of significant changes in length and body weight and blood glucose.
Effects of enriched environment on maximal lactate steady state of wistar rats
Keywords: Enriched environment; Lactate; Physical activity